Memorandum of understanding between Universiti Teknologi MARA and Perbadanan Nasional Berhad / Fakulti Perakaunan - Universiti Teknologi MARA, Fakulti Perakaunan (Universiti Teknologi MARA (UiTM), 2021)
UiTM and PNB will endeavour to strengthen, promote and develop cooperation on the basis of equality and mutual benefit.